2020
DOI: 10.1080/00913847.2020.1796469
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic confirmation of femoral button deployment avoids post-operative X-ray in ACL reconstruction

Abstract: Background: Anterior cruciate ligament reconstruction (ACLR) with cortical fixation adjustable-loop devices are associated with high potential risk of button malpositioning or interposition of the soft tissue between lateral femoral cortex and the button. Surgeons usually use X-rays to check and avoid button malposition and soft tissue interposition. Arthroscopic visualization of button position through the lateral gutter has been described. With this technique, it is possible for identification and correction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A similar study conducted by Matassi et al. 7 also investigated the benefits of using arthroscopic confirmation of proper button placement. This study used a direct visualization perspective through the anterolateral portal analogous to the view we described as extra-articular.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A similar study conducted by Matassi et al. 7 also investigated the benefits of using arthroscopic confirmation of proper button placement. This study used a direct visualization perspective through the anterolateral portal analogous to the view we described as extra-articular.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequently, zero cases of tissue interposition were reported postoperatively when arthroscopic confirmation was used, compared with 8% of cases presenting this complication without using arthroscopic confirmation. 7 …”
Section: Discussionmentioning
confidence: 99%
“… 10 Arthroscopic direct visualization of the button deployment is a more effective method. Several studies have reported that the proper position was achieved through an arthroscopic view of the lateral gutter of the knee or an iliotibial band portal 4 , 8 , 11 , 16 in ACLR. It was reported that the femoral button placed with direct visualization was more likely to have an optimal position directly on the femoral cortex compared with indirect methods (0% vs 8.8%; P = .046).…”
Section: Discussionmentioning
confidence: 99%